Clarendon News - January 26, 1939 - (:unkn) unknown (My University, 1939)
Microfilm provided by the Panhandle-Plains Historical Museum and Clarendon ISD.
This was a weekly newspaper for Clarendon in Donley County, Texas founded in 1902 by A. M. Beville. This Clarendon News is unrelated to the earlier title of the same name. This publication continued under this name until 1945 when the newspaper was absorbed by the Donley County Leader.
Keywords: Clarendon News; Clarendon (Tex.)--Newspapers.; Donley County (Tex.)--Newspapers.